PENGARUH PEMBERIAN EKSRTRAK KULIT BUAH NAGA (Hylcereus polyrhizus) DAN CIPLUKAN (Physalis angulata L.) MELALUI AIR MINUM TERHADAP OFFAL EKSTERNAL ITIK BALI JANTAN - Larasati T. D.; I. M. Nuriyasa; G. A. M. K. Dewi (Fakultas Peternakan Universitas Udayana, 2025)
This study aims to determine the effect of giving dragon fruit peel extract and ciplukan extract through drinking water on the external offal of male Balinese ducks. This research was conducted at Sesetan Farm, Faculty of Animal Husbandry, Udayana University, located at Jalan Raya Sesetan, Denpasar, Bali for 5 weeks. The design used was a completely randomized design (CRD) with 5 treatments and 4 replicates and each replicate contained 5 one-week-old ducks. The treatments given are, P1: Giving drinking water without dragon fruit peel extract and ciplukan extract, P2: Giving drinking water with 5% dragon fruit peel extract, P3: Giving drinking water with 5% ciplukan extract, P4: Giving drinking water with a mixture of 2.5% ciplukan extract and 2.5% dragon fruit peel extract, P5: Giving drinking water with a mixture of 5% ciplukan extract and 5% dragon fruit peel extract. The variables observed were the percentage of head, neck, legs, blood, and fur. The results showed that the provision of dragon fruit peel extract and ciplukan did not have a significant effect (P>0.05) on the percentage of external offal (head, neck, legs, blood and feathers) of male Balinese ducks aged 6 weeksThe results of the study showed that the administration of 5% dragon fruit peel extract, 5% ciplukan, a mixture of dragon fruit peel and ciplukan extracts each 2.5%, and a mixture of dragon fruit peel extract and ciplukan 5% each did not have a significant effect (P>0.05) on the percentage of external offal (head, neck, feet, blood and feathers) of 6 week old male Bali ducks.. It can be concluded that the administration of 5% dragon fruit peel extract, 5% ciplukan extract, a mixture of dragon fruit peel and ciplukan extracts of 2.5% each, and a mixture of dragon fruit peel and ciplukan extracts of 5% each through drinking water had no effect on the percentage of external offal (head, neck, feet, blood and feathers) of male Balinese ducks aged 6 weeks. ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh pemberian ekstrak kulit buah naga dan ekstrak ciplukan melalui air minum terhadap offal eksternal itik bali jantan. Penelitian ini dilaksanakan di Farm Sesetan, Fakultas Peternakan Universitas Udayana, yang berlokasi di Jalan Raya Sesetan, Denpasar, Bali selama 5 minggu. Rancangan yang digunakan adalah Rancangan Acak Lengkap (RAL) dengan 5 perlakuan dan 4 ulangan dan setiap ulangan berisi 5 ekor itik berumur satu minggu. Adapun perlakuan yang diberikan yaitu, P1: Pemberian air minum tanpa ekstrak kulit buah naga dan ekstrak ciplukan, P2 : Pemberian air minum dengan 5% ekstrak kulit buah naga, P3 : Pemberian air minum dengan 5% ekstrak ciplukan, P4 : Pemberian air minum dengan campuran 2,5% ekstrak ciplukan dan 2,5% ekstrak kulit buah naga, P5 : Pemberian air minum dengan campuran 5% ekstrak ciplukan dan 5% ekstrak kulit buah naga. Variabel yang diamati adalah persentase kepala, leher, kaki, darah, dan bulu. Hasil penelitian menunjukan bahwa pemberian ekstrak kulit buah naga 5%, ciplukan 5%, campuran ekstrak kulit buah naga dan ciplukan masing-masing 2,5%, dan campuran ekstrak kulit buah naga dan ciplukan masing-masing 5% tidak memberikan pengaruh yang nyata (P>0,05) terhadap persentase offal eksternal (kepala, leher, kaki, darah dan bulu) itik bali jantan umur 6 minggu. Dapat disimpulkan bahwa pemberian ekstrak kulit buah naga 5%, ekstrak ciplukan 5%, campuran ekstrak kulit buah naga dan ciplukan masing-masing 2,5%, dan campuran ekstrak kulit buah naga dan ciplukan masing-masing 5% melalui air minum tidak berpengaruh terhadap persentase offal eksternal itik bali jantan umur 6 minggu.